TEKNIK MEMBACA ARTIKEL BERBAHASA INGGERIS - Ihsan, Muhammad (State Institute of Islamic Studies (IAIN) Palu, 2005)
This article discusses techniques of reading English article. There are some techniques that can be applied in reading English articles, each of which lies on the information the reader needs from the article. The first scanning can be applied by readers to get specific information from the article; preview technique can be applied to relate readers’ knowledge to the issues discussed in the article; the second scanning technique can be applied to conduct review in the respect of general aim of the article, to clarify prior ideas and to verify as well as to give emphasis on certain ideas containing in the article. Kata Kunci: Artikel, Scanning, Review